Orange photons (623 nm) resulted in similar or greater lettuce growth than red photons (660 nm): comparative effects on morphology, photon capture, and photosynthesis - Kang, Seonghwan; Zhen, Shuyang (Frontiers in Plant Science, 2025)
Photosynthetic efficiency is wavelength-dependent. Previous studies found that photons between ~600–625 nm (herein referred to as ‘orange photons’) resulted in the highest quantum yield (i.e., moles of CO2 fixed per mole of absorbed photons), followed by ~650–675 nm red photons. However, these findings were based on short-term, single-leaf measurements, and limited information is available on the long-term effects of orange photons on plant growth and photosynthesis. Orange photons may differentially influence photoreceptors such as cryptochromes and phytochromes compared to red photons, leading to changes in plant morphology and phytochemical accumulation. Therefore, our objective was to quantify the effects of orange versus red photons on plant growth, morphology, and photosynthetic responses. Two lettuce cultivars, green butterhead ‘Rex’ and red oakleaf ‘Rouxai’, were grown in a growth chamber under four light spectral treatments using blue (B; 444 nm), green (G; 536 nm), orange (O; 623 nm), red (R; 660 nm), and far-red (FR; 730 nm) light emitting diodes (LEDs): 1) B50G25O175, 2) B50G25R175, 3) B50G25O137.5FR37.5 (O+FR), and 4) B50G25R137.5FR37.5 (R+FR). Subscripts indicate photon flux density in µmol m-2 s-1; all treatments had the same total photon flux density of 250 µmol m-2 s-1. Orange photons generally resulted in similar or greater plant growth than red photons. Specifically, in the absence of FR, replacing red with orange photons increased total leaf area and shoot dry weight in ‘Rex’ by 12-15%, likely resulting from cryptochrome deactivation. In contrast, orange photons reduced anthocyanin accumulation in red lettuce ‘Rouxai’ without affecting yield. The inclusion of FR photons significantly increased leaf area and shoot biomass in both cultivars, with similar growth observed under the O+FR and R+FR treatments. While leaf photosynthesis rate of ‘Rex’ was lower under orange measurement light on an incident photon basis, quantum yield was generally higher under orange than red light. Given that current orange LEDs are less energy-efficient than red LEDs, it is important to consider both the plant growth benefits and energy costs when using orange photons in controlled environments.